Facile synthesis of graphene oxide/palygorskite composites for Pb(II) rapid removal from aqueous solutions - Zeng, Wen-Juan (Water science and technology : a journal of the International Association on Water Pollution Research, 2019)
As a kind of earth-abundant and cheap natural clay mineral, palygorskite (Pal) was facilely modified by grafting with graphene oxide (GO) to fabricate GO/Pal composites for rapid removal of Pb(II) from aqueous solutions. The results of characterization confirmed that the GO/Pal composites were successfully grafted between GO sheets and Pal nanorods. The effects of pH, adsorbent dosage, adsorption time, initial Pb(II) concentration and temperature on the adsorption of Pb(II) onto the GO/Pal composites as adsorbents were systematically investigated. The maximum adsorption capacity over 106.6 mg/g was obtained within a short adsorption time of less than 1 h even at 298.15 K. The adsorption of Pb(II) was a fast process that more accurately followed the pseudo-second-order kinetic equation. This process also could be described better with the Langmuir equation model than the Freundlich model. The negative values of ΔG° and the positive values of ΔH° and ΔS° indicated that it was a spontaneous, endothermic and entropy-increasing adsorption process. Compared with pristine Pal and GO powders, such the GO/Pal composites as a cost-efficient and eco-friendly adsorbents could significantly improve the adsorption properties of Pb(II) and would have potential application in the industrial wastewater treatment for rapid removal of Pb(II)